Accuracy Enhancement of Electrotechnical System for Bulk Material Batching; MATEC Web of Conferences; Vol. 19 : The 2nd International Youth Forum "Smart Grids", Tomsk, Russia, October 6-10, 2014 - Bukreev V. G. Viktor Grigorievich (2014, 2014)
Title screen